Lead, Zinc and Cadmium in Root Crops from Mineralized Galena-Sphalerite Mining Areas and Environment - Onyedika, G.O.; Nwosu, G.U. (Pakistan Journal of Nutrition, 2008)
Concentrations of the metals leads, cadmium and zinc were estimated in root crops: Cassava (Manihot esculenta crantz), yam (Dioscorea rotundata), potato (Ipomea batatas) and cocoyam (Colocosia esculenta) harvested in some mineralized areas of galena and sphalerite deposits using atomic absorption spectrophotometer. The Investigation showed that the sample analyzed contained lead concentration ranging from 0.030-0.190 mg/kg. Cadmium levels were in the concentration range of 0.136-2.633 mg/kg in all crops, while zinc concentration ranged from 0.340-3.890 mg/kg. There was no significance difference observed between the levels of contamination of the different crops, while high variation in concentration was observed in the level of predominance of heavy metals in different location. These results reflected higher concentration of metals in selected crops from these zone.